Circulating non-coding RNAs as biomarkers in coronary artery disease - Petković, Aleksa; Erceg, Sanja; Munjas, Jelena; Ninić, Ana; Sopić, Miron (Archives of Pharmacy, 2022)
Coronary artery disease (CAD) is a leading cause of mortality worldwide. Atherosclerosis involves an interplay of different pathological mechanisms, such as progressive inflammation, abnormal lipid metabolism, and oxidative stress, and as such represents the basic pathological phenomenon underlying CAD. Atherosclerotic plaque narrows the lumen of coronary arteries, creating an ischemic environment for the heart muscle, which finally leads to clinical complications, such as acute myocardial infarction. Currently, there are no biomarkers that could predict plaque stability or major adverse cardiovascular events (MACE). Numerous functional non-coding RNA (ncRNA) species influence basic cellular functions, and as such play a role in the development and progression of CAD. Of these ncRNAs, micro RNAs (miRNAs) and long non-coding RNAs (lncRNAs) are the most investigated. Considering that ncRNAs detected in extracellular fluids can originate from different cells, circulating ncRNAs are being intensively investigated as potential biomarkers in the diagnosis and prognosis of CAD. In the following paper, we provide current insights into potential molecular mechanisms by which miRNAs and lncRNAs contribute to the pathology of CAD and discuss their potential role as biomarkers in diagnosis and prognosis of disease.